Cathode active material and preparation method thereof, secondary battery and electric device
By introducing element A into the nickel-manganate positive electrode material, the dissolution of Mn element and the formation of stable bonds is solved, and the cycle stability of the battery is improved.
Patent Information
- Application Number
- CN202411879518.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
The dissolution of manganese during spinel nickel-manganate during circulation leads to battery capacity loss and degradation of cycling performance.
By introducing A elements (such as Al, F, W) into the nickel-manganate positive electrode material, the mass proportion of A elements is adjusted during the sintering process, the growth of {110} plane is suppressed, thereby reducing the dissolution of Mn elements and forming Me-A or A-O bonds to improve material stability.
The dissolution of Mn element is effectively inhibited, and the stability of the positive electrode active material and the cycle stability of the secondary battery are improved.
Smart Images

Figure BDA0005199048400000111 
Figure BDA0005199048400000121
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, secondary batteries and electrical devices. Background Art
[0002] With the development of new energy, the development of lithium-ion batteries has become increasingly important. 0.5 Mn 1.5 O4) is used in high energy density power battery systems because of its high reaction potential (>4.6V), high theoretical specific capacity (>140mAh / g), and low cost. However, the dissolution of manganese in the cycle of spinel nickel manganese oxide will lead to the loss of battery capacity and the decline of cycle performance.
[0003] It can be seen that a new lithium nickel manganese oxide material is urgently needed to alleviate the problem that the dissolution of manganese in the existing spinel lithium nickel manganese oxide cycle process will lead to loss of battery capacity and degradation of cycle performance. Summary of the invention
[0004] The present invention introduces element A into the positive electrode material of lithium nickel manganese oxide, effectively inhibits the dissolution of Mn element in the positive electrode active material, improves the stability of the positive electrode active material, and thus improves the cycle stability of the secondary battery. Specifically, by introducing element A in the primary sintering process, by adjusting the mass proportion of element A in the primary sintering, the proportion of element A in the positive electrode active material is regulated, and after high-temperature sintering, the positive electrode lithium nickel oxide material Li doped with element A is obtained. a Ni x Mn y O b A z T r In the present application, since the A element will inhibit the growth of the {110} face during the sintering process, thereby inhibiting the dissolution of the Mn element; at the same time, the A element has a stronger electronegativity, and the stability of the Me-A bond is better than that of Me-O, which is beneficial to the stability of the positive electrode active material. The two work together to improve the cycle stability of the battery.
[0005] The present application provides a positive electrode active material having the following chemical formula: Li a Ni x Mn y O b A z T r, wherein 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, and wherein A is one or more of Al, F, W, optionally, T is a metal doping element, and 0≤r<0.1, optionally, T is selected from at least one of Mg, Zr, Ti, La, Sr. In the present application, the above-mentioned positive electrode active material is a positive electrode lithium nickelate material doped with element A, and optionally A is F. By doping with element A, the growth of the {110} face can be effectively inhibited, thereby inhibiting the reduction of Mn element dissolution. It should be noted that Me represents a metal element, and for the positive electrode active material of the above chemical formula, Me represents Ni and / or Mn.
[0006] In some embodiments, the A element is uniformly dispersed in the positive electrode active material. In the present application, the A element forms a Me-A or AO bond, and the molar proportion of the A element is 0.006%-7% based on the total molar amount of the positive electrode active material. In some embodiments, the crystal plane thickness D of the {110} crystal plane in the positive electrode active material is hkl Between 0.125 and 0.140.
[0007] Some other embodiments of the present application provide a method for preparing a positive electrode active material, comprising: mixing a lithium salt and a nickel-manganese precursor, adding an additive to obtain a mixture; and sintering the mixture to obtain the above-mentioned positive electrode active material, wherein the additive comprises an A element, and based on the total molar amount of the positive electrode active material, the molar ratio of the A element is 0.006%-7%-, and wherein the chemical formula of the nickel-manganese precursor is Ni x Mn y T r (OH)2, wherein 0.225≤x≤0.275, 0.725≤y≤0.775, T is a metal doping element, optionally, T is selected from at least one of Mg, Zr, Ti, La, Sr, and 0≤r<0.1. In some embodiments, the additive includes one or more of Al2O3, Al(OH)3, polyvinylidene fluoride, WO3, lithium fluoride, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(difluorosulfonyl imide), and lithium bis(trifluoromethylsulfonyl imide).
[0008] In some embodiments, the molar ratio of lithium in the lithium salt to the metal element in the nickel manganese precursor is 0.48-0.55: 1. In some embodiments, the sintering temperature is 700° C.-1100° C., and the sintering time is 8 h-14 h. In some embodiments, the lithium salt is selected from one or both of lithium carbonate and lithium hydroxide.
[0009] Some embodiments of the present application also provide a secondary battery, including a positive electrode plate, wherein the positive electrode plate includes the above-mentioned positive electrode active material.
[0010] Still other embodiments of the present application provide an electrical device including the secondary battery.
[0011] In summary, the present application suppresses the dissolution of the Mn element in the positive electrode active material by doping the A element, improves the stability of the positive electrode active material, and improves the cycle stability of the secondary battery. DETAILED DESCRIPTION
[0012] In the new energy field, the cycle performance of the battery is very important. The positive electrode active material provided by the present application effectively alleviates the dissolution of manganese in the positive electrode active material spinel nickel manganese oxide during the cycle, which will lead to the loss of battery capacity and the decrease of cycle performance. Based on this, the present application provides an element A doped positive electrode lithium nickel oxide material. Specifically, the present application provides a positive electrode active material having the following chemical formula: Li a Ni x Mn y O b A z T r , wherein 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, and wherein A is one or more of Al, F, and W, optionally, A is F, T is a metal doping element, optionally, T is selected from at least one of Mg, Zr, Ti, La, and Sr, and 0≤r<0.1. In the present application, the positive electrode active material is a positive electrode lithium nickelate material doped with element A, optionally A is F, and by doping with element A, the growth of the {110} face can be effectively inhibited, thereby inhibiting the reduction of Mn element dissolution. It should be noted that Me represents a metal element, and for the positive electrode active material of the above chemical formula, Me represents Ni and / or Mn. In the following embodiments, Me represents Ni and Mn.
[0013] In some embodiments, the A element is uniformly dispersed in the positive electrode active material. In the present application, the A element forms a Me-A or AO bond, and the molar proportion of the A element is 0.006%-7% based on the total molar amount of the positive electrode active material. In some embodiments, the crystal plane thickness D of the {110} crystal plane in the positive electrode active material is hkl Between 0.125 and 0.140. Specifically, D hkl Represents the crystal plane thickness. The crystal plane thickness of the {110} crystal plane is calculated according to the following Scherrer formula {110}D hkl :D hkl =Kλ / (βcosθ), where D hklrepresents the crystal plane thickness, K is the Scherrer constant (usually 0.9), λ is the wavelength of the A-ray, β is the peak width, and θ is the diffraction angle. This formula has two uses: (1) When the D of a known crystal is hkl By measuring θ, the characteristic A-ray λ is calculated, and the element that produces the characteristic A-ray is determined by λ. This is mainly used in A-ray fluorescence spectrometers and electron probes; and (2) when the wavelength of the incident A-ray is known, the crystal plane thickness D is calculated by measuring θ. hkl . And through the crystal plane thickness, the crystal structure is determined or the phase analysis is performed. In this application, the growth of the {110} plane is effectively inhibited by doping with the A element, thereby reducing the dissolution of the Mn element; at the same time, Me-A or AO bonds are formed, and the two play a synergistic role to improve the material stability and improve the battery cycle stability.
[0014] Some other embodiments of the present application provide a method for preparing a positive electrode active material, comprising: mixing a lithium salt and a nickel-manganese precursor, adding an additive to obtain a mixture; and sintering the mixture to obtain the above-mentioned positive electrode active material, wherein the additive comprises an A element, and based on the total molar amount of the positive electrode active material, the molar ratio of the A element is 0.006%-7%-, and wherein the chemical formula of the nickel-manganese precursor is Ni x Mn y T r (OH)2, wherein 0.225≤x≤0.275, 0.725≤y≤0.775, T is a metal doping element, and 0≤r<0.1, optionally, T is selected from at least one of Mg, Zr, Ti, La, and Sr. In some embodiments, the additive includes one or more of Al2O3, Al(OH)3, polyvinylidene fluoride, WO3, lithium fluoride, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(difluorosulfonyl imide), and lithium bis(trifluoromethylsulfonyl imide). In some embodiments, the chemical formula of the nickel manganese precursor is Ni x Mn y In the present application, element A is introduced in a single sintering process, and other doping elements T are optionally introduced. By adjusting the proportion of element A in the raw materials, the molar proportion of element A in the positive electrode active material is regulated, and after high-temperature sintering, the positive electrode lithium nickel oxide material Ni doped with element A is obtained. x Mn y T r (OH)2. During the sintering process, element A will inhibit the growth of the {110} plane, thereby inhibiting the dissolution of the Mn element. At the same time, element A has a stronger electronegativity, and the stability of the Me-F bond is better than that of Me-O, which is beneficial to the stability of the positive electrode active material. Therefore, the two work together to improve the cycle stability of the battery material.
[0015] In some embodiments, the molar ratio of lithium in the lithium salt and the metal element in the nickel manganese precursor is 0.48-0.55:1. In some embodiments, the sintering temperature is 700℃-1100℃, and the sintering time is 8h-14h. In some embodiments, the lithium salt is selected from one or two of lithium carbonate and lithium hydroxide. The specific preparation method of the positive electrode active material is: lithium salt: precursor is mixed according to the molar ratio of lithium (Li) in the lithium salt and the metal element (Me) in the nickel manganese precursor of 0.48-0.55:1, and an additive containing element A is added, wherein the molar proportion of element A is 0.006%-7% based on the total molar amount of the positive electrode active material, and it is placed in an air atmosphere and sintered for 8-14h at a sintering temperature of 700-1100℃ to obtain the target material, that is, the nickel manganese spinel material doped with element A Li a Ni x Mn y O b A z T r , wherein 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, A is one or more of Al, F, and W, T is a metal doping element, optionally T is selected from at least one of Mg, Zr, Ti, La, and Sr, and 0≤r<0.1. In the present application, the A element is uniformly distributed in the positive electrode active material. It can be seen from CP-EDS (electron tube core classification test) and XPS test (X-ray photoelectron spectroscopy analysis) that the A element forms a Me-A bond, and the molar proportion of the A element is measured to be 0.006-7%. According to the XRD (X-ray diffraction) test, the {110} crystal plane thickness is calculated by the Scherrer formula known in the art to characterize the growth of the {110} plane. In the present application, the crystal plane thickness D of the {110} crystal plane in the positive electrode active material hkl Between 0.125 and 0.140.
[0016] Some embodiments of the present application also provide a secondary battery, including a positive electrode sheet, wherein the positive electrode sheet includes the above-mentioned positive electrode active material. For a non-aqueous electrolyte battery, the secondary battery also includes a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet. For a solid-state battery, the secondary battery does not include a separator and includes a solid electrolyte. The present application is described by taking a non-aqueous electrolyte battery as an example.
[0017] Some other embodiments of the present application also provide an electrical device including the secondary battery. In some specific embodiments, the secondary battery is a lithium-ion battery, and the positive electrode sheet of the lithium-ion battery includes a positive electrode active material and a positive electrode current collector, and the positive electrode active material is Li a Ni xMn y O b A z T r , wherein 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, A is one or more of Al, F, and W, T is a metal doping element, and 0≤r<0.1, optionally, T is selected from at least one of Mg, Zr, Ti, La, and Sr. In some embodiments, the positive electrode collector may include aluminum foil. The negative electrode includes a material and a negative electrode collector, and the negative electrode material includes a graphite material, specifically, it may include one or more of low-graphitized carbon, easily graphitized carbon, artificial graphite, natural graphite, and the like. In some embodiments, the negative electrode collector may include copper foil. The separator includes at least one selected from polyethylene, polypropylene, polyethylene terephthalate, polyimide, and aramid. The electrolyte may include any commonly used electrolyte in the art, and in some embodiments, the electrolyte includes a lithium salt and a non-aqueous solvent. The lithium salt may be selected from LiPF6. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a chain carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof. Examples of chain carbonate compounds are diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC) and a combination thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) and a combination thereof. An example of a fluorinated carbonate compound is fluoroethylene carbonate (FEC). Examples of carboxylate compounds are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, caprolactone, methyl formate and a combination thereof, etc.
[0018] The positive electrode sheet, separator, and negative electrode sheet are wound, folded, or stacked in sequence to form an electrode assembly, and then packaged in, for example, an aluminum-plastic film, injected with electrolyte, formed, and packaged to produce a lithium-ion battery.
[0019] Those skilled in the art will understand that the above-described method for preparing a lithium-ion battery is only an example, and other commonly used methods in the art may be used without departing from the contents disclosed in the present application.
[0020] Some specific embodiments and comparative examples are listed below to better illustrate the present application.
[0021] Example 1
[0022] (1) Preparation of positive electrode active materials
[0023] Lithium carbonate was used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, according to the lithium (Li) and Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.52:1, and the additives of aluminum oxide and aluminum hydroxide (mass ratio is 1:1) are added to obtain a mixture, wherein A is Al (aluminum), and based on the total molar amount of the positive electrode active material, the molar amount of the Al element accounts for 0.14%. The mixture is sintered at a sintering temperature of 920°C in an air atmosphere for 13 hours to obtain Al-doped nickel-manganese spinel material Li 1.04 Ni 0.5 Mn 1.5 O 3.99 Al 0.01 .
[0024] (2) Preparation of positive electrode sheet
[0025] The Al-doped nickel-manganese spinel material prepared above is used as the positive electrode active material (positive electrode main material), and the conductive agent carbon black (Super P) and the binder polyvinylidene fluoride (PVDF) are added at the same time. The mass ratio of the positive electrode active material, the conductive agent carbon black (SuperP) and the binder polyvinylidene fluoride (PVDF) is 97:1.5:1.5. The specific preparation steps of the positive electrode sheet are: the nickel-manganese spinel material, Super P, and PVDF are mixed in the above proportions, and then nitrogen methyl pyrrolidone (NMP) is gradually added with high-speed stirring (speed of 2000r / min-3000r / min) to prepare a positive electrode slurry with a certain viscosity (1.5Pa·s to 5.0Pa·s). Then the prepared slurry is evenly coated on aluminum foil, placed in a blast drying oven and dried at 120°C for 10 minutes, and finally the dried electrode sheet is rolled, cut, and made into a positive electrode sheet.
[0026] (3) Preparation of negative electrode sheet
[0027] The negative electrode active material graphite, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose and the adhesive styrene butadiene rubber are mixed in a mass ratio of 97:1:1:1, and after adding deionized water, the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the copper foil current collector, and then dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the negative electrode sheet.
[0028] (4) Diaphragm
[0029] The separator is a polyethylene (PE) porous polymer film of 8 μm to 14 μm, with an air permeability of 150 s / 100 mL to 350 s / 100 mL and a porosity of 30% to 50%.
[0030] (5) Electrolyte
[0031] The electrolyte is lithium salt LiPF6, and the mass content of LiPF6 is 4-24wt% based on the total mass of the electrolyte.
[0032] The prepared positive electrode sheet and the graphite negative electrode sheet are assembled into a 1.5Ah soft pack battery. After the injection, formation and aging processes, a lithium-ion battery is obtained.
[0033] Example 2
[0034] The preparation method is consistent with that of Example 1, except that in Example 2, lithium hydroxide monohydrate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.50:1, and the additive tungsten oxide is added to obtain a mixture, wherein A is W, and based on the total molar amount of the positive electrode active material, the molar proportion of the W element is 3.4%. The mixture is sintered at a sintering temperature of 900°C in an air atmosphere for 11 hours to obtain a W-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 4.0 W 0.25 .
[0035] Example 3
[0036] The preparation method is consistent with that of Example 1, except that in Example 3, lithium carbonate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.52:1, and the additives lithium fluoride and lithium hexafluoroarsenate (mass ratio is 1:1) are added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 0.14%. The mixture is sintered at a sintering temperature of 920°C in an air atmosphere for 13 hours to obtain a F-doped nickel-manganese spinel material Li 1.04 Ni 0.5 Mn 1.5 O 3.99F 0.01 .
[0037] Example 4
[0038] The preparation method is consistent with that of Example 1, except that lithium carbonate is used as the lithium salt in Example 4, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.49:1, and the additive lithium hexafluoroarsenate is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 4.3%. The mixture is sintered at a sintering temperature of 880°C in an air atmosphere for 12 hours to obtain a F-doped nickel-manganese spinel material Li 0.98 Ni 0.5 Mn 1.5 O 3.70 F 0.30 .
[0039] Example 5
[0040] The preparation method is consistent with that of Example 1, except that lithium carbonate is used as the lithium salt in Example 5, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.49:1, and the additive lithium hexafluoroarsenate is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 5.0%. The mixture is sintered at a sintering temperature of 940°C in an air atmosphere for 12 hours to obtain a F-doped nickel-manganese spinel material Li 0.98 Ni 0.5 Mn 1.5 O 3.65 F 0.35 .
[0041] Example 6
[0042] The preparation method is consistent with that of Example 1, except that lithium carbonate is used as the lithium salt in Example 6, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75The molar ratio of the metal element (Me) in (OH)2 is 0.53:1, and the additive lithium fluoride is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 2.8%. The mixture is sintered at a sintering temperature of 890°C in an air atmosphere for 12 hours to obtain a F-doped nickel-manganese spinel material Li 1.06 Ni 0.5 Mn 1.5 O 3.80 F 0.20 .
[0043] Example 7
[0044] The preparation method is consistent with that of Example 1, except that in Example 7, lithium hydroxide monohydrate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.50:1, and the additive lithium hexafluorophosphate is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 3.6%. The mixture is sintered at a sintering temperature of 900°C in an air atmosphere for 11 hours to obtain a F-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 3.75 F 0.25 .
[0045] Example 8
[0046] The preparation method is consistent with that of Example 1, except that in Example 8, lithium hydroxide monohydrate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The mixture is mixed with the metal element (Me) in the (OH)2 at a molar ratio of 0.50:1, and the additive lithium bis(difluorosulfonyl)imide is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 2.1%. The mixture is sintered at a sintering temperature of 980°C in an air atmosphere for 11 hours to obtain a F-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 3.85 F 0.15 .
[0047] Example 9
[0048] The preparation method is consistent with that of Example 1, except that in Example 9, lithium hydroxide monohydrate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, according to the lithium (Li) and Ni 025 Mn 0.75 The mixture is mixed with the metal element (Me) in the (OH)2 at a molar ratio of 0.50:1, and the additive lithium bis(trifluoromethylsulfonyl)imide is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 1.3%. The mixture is sintered at a sintering temperature of 900°C in an air atmosphere for 11 hours to obtain a F-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 3.91 F 0.09 .
[0049] Example 10
[0050] The preparation method is consistent with that of Example 1, except that zirconium oxide (ZrO2) is added in Example 10. Based on the total molar amount of the positive electrode active material, the molar proportion of the Zr element is 2.08%, thereby obtaining the Al-doped nickel-manganese spinel material Li with other doping elements Zr. 1.04 Ni 0.5 Mn 1.5 O 3.99 Al 0.01 Zr 0.15 .
[0051] Comparative Example 1
[0052] The preparation method is consistent with that of Example 1, except that lithium carbonate is used as the lithium salt in Comparative Example 1, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, according to the lithium (Li) and Ni 025 Mn 0.75 The mixture was mixed with the metal element (Me) in OH2 at a molar ratio of 0.50:1 to obtain a mixture without using any additives. The mixture was sintered at a sintering temperature of 880°C in an air atmosphere for 10 hours to obtain a nickel-manganese spinel material Li 1。0 Ni 0.5 Mn 1.5 O4.
[0053] Comparative Example 2
[0054] The preparation method is consistent with that of Example 1, except that in Comparative Example 2, lithium hydroxide monohydrate is used as the lithium salt, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The mixture was mixed with the metal element (Me) in (OH)2 at a molar ratio of 0.51:1 to obtain a mixture without using any additives. The mixture was sintered at a sintering temperature of 920°C in an air atmosphere for 10 hours to obtain the nickel-manganese spinel material Li 1.02 Ni 0.5 Mn 1.5 O4.
[0055] Comparative Example 3
[0056] The preparation method is consistent with that in Example 1, except that lithium carbonate is used as the lithium salt in Comparative Example 4, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.50:1, and the additive aluminum oxide is added to obtain a mixture, wherein A is Al, and based on the total molar amount of the positive electrode active material, the molar proportion of the Al element is 7.9%. The mixture is sintered at a sintering temperature of 820°C in an air atmosphere for 10 hours to obtain an Al-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 4.00 Al .0.6 .
[0057] Comparative Example 4
[0058] The preparation method is consistent with that of Example 1, except that lithium carbonate is used as the lithium salt in Comparative Example 5, and Ni 025 Mn 0.75 (OH)2 is used as a nickel-manganese precursor, and the lithium (Li) in the lithium salt and the Ni 025 Mn 0.75 The molar ratio of the metal element (Me) in (OH)2 is 0.50:1, and the additive lithium fluoride is added to obtain a mixture, wherein A is F (fluorine), and based on the total molar amount of the positive electrode active material, the molar proportion of the F element is 14.4%. The mixture is sintered at a sintering temperature of 920°C in an air atmosphere for 10 hours to obtain a F-doped nickel-manganese spinel material Li 1.0 Ni 0.5 Mn 1.5 O 3.00 F1.01 .
[0059] XRD test of powder material of positive electrode active material
[0060] The powder material of the positive electrode active material is made into a thin sheet and the surface is ensured to be smooth; the thin sheet is placed on the sample stage and the scanning range is set to 0-80° and the time is 40 minutes. The crystal plane thickness {110} D of the {110} crystal plane is calculated according to the following Scherrer formula hkl :
[0061] D hkl =Kλ / (βcosθ), where D hkl represents the crystal plane thickness, K is the Scherrer constant (usually 0.9), λ is the wavelength of the X-ray, β is the peak width, and θ is the diffraction angle.
[0062] Secondary battery performance test method:
[0063] (1) Cyclic performance test
[0064] In an oven at 25°C, the secondary batteries in Examples 1-10 and Comparative Examples 1-4 were cyclically charged and discharged at a current of 1C in a specified potential range (3.5V-5V), and the discharge capacity of each cycle was recorded. The test was terminated when the battery capacity was less than or equal to 80% of the first cycle capacity for the first time, and the number of cycles was recorded as the cycle life of the battery.
[0065] (2) Mn content in electrolyte after 150cl cycle (ppm)
[0066] In an oven at room temperature, cyclic charge and discharge were performed in a specified potential range (3.5V-5V) at a current of 1C. After 150cl of cycles, the secondary batteries in Examples 1-10 and Comparative Examples 1-4 were disassembled, the electrolytes in the secondary batteries were collected, and the Mn content in the electrolytes was tested.
[0067] The test results are shown in Table 1 below.
[0068] Table 1. Performance test results of secondary batteries (lithium ion batteries) of Examples 1-10 and Comparative Examples 1-4
[0069]
[0070]
[0071] From the above results, it can be seen that by comparing Examples 1-10 and Comparative Examples 1-2, the positive electrode active material provided by the present application has the following chemical formula: Li a Ni x Mn y O b Az T r , wherein 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, and wherein A is one or more of Al, F, W, T is a metal doping element, and 0≤r<0.1, optionally, T is selected from at least one of Mg, Zr, Ti, La, Sr. Since the A element has a stronger electronegativity, the Me-A bond stability is better than Me-O, which is beneficial to the stability of the positive electrode active material, thereby improving the cycle stability of the battery material. From the above data, it can be seen that when A is F, the effect is better, and the cycle stability of the battery material is better. Furthermore, the chemical formula of the nickel manganese precursor is Ni 025 Mn 0.75 In this application, element A is introduced in a sintering process, and the mass proportion of element A in the positive electrode active material is regulated by adjusting the proportion of element A in the lithium salt. After sintering at high temperature (700℃-1100℃) (8h-14h), the positive electrode lithium nickel oxide material Li doped with element A is obtained. a Ni x Mn y O b A z T r During the sintering process, element A will inhibit the growth of the {110} plane, thereby inhibiting the dissolution of the Mn element. At the same time, element A has a stronger electronegativity, and the stability of the Me-F bond is better than that of Me-O, which is beneficial to the stability of the positive electrode active material. Therefore, the two work together to improve the cycle stability of the battery material.
[0072] Furthermore, it can be seen from Example 5 that when the A element is F, the battery has the best cycle stability, the cycle can reach 800cl, and the Mn content in the electrolyte is 39ppm after 150cl of cycle.
[0073] By comparing Examples 1-10 and Comparative Examples 1-4, it can be seen that in the present application, the positive electrode lithium nickel oxide material Li doped with element A a Ni x Mn y O b A z T r , and 0.0005≤z≤0.5, when the molar proportion of element A is in the range of 0.006%-7%, the cycle performance of the battery can be effectively improved. When the molar proportion of element A is less than the modified range, the growth of the {110} plane cannot be effectively inhibited; when it exceeds this range (such as 7.9% and 14.4% in comparative example 3), the doping element causes a certain degree of damage to the crystal structure, and the cycle performance of the battery decreases.
[0074] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.
Claims
1. A positive electrode active material, characterized in that: Has the following chemical formula: Li a Ni x Mr y O b A z T r , Wherein, 0.95≤a≤1.05, 0.45≤x≤0.55, 1.45≤y≤1.55, 3.5≤b≤4.05, 0.0005≤z≤0.5, and wherein A is one or more of Al, F, and W, T is a metal doping element, and 0≤r<0.
1.
2. The positive electrode active material according to claim 1, characterized in that T is selected from at least one of Mg, Zr, Ti, La, and Sr.
3. The positive electrode active material according to claim 1, characterized in that The thickness D of the {110} crystal plane in the positive electrode active material hkl Between 0.125 and 0.
140.
4. A method for preparing a positive electrode active material, characterized in that: include: Mixing lithium salt and nickel manganese precursor, and adding additives to obtain a mixture; as well as The mixture is sintered to obtain the positive electrode active material according to any one of claims 1 to 4, The additive comprises an element A, and based on the total molar amount of the positive electrode active material, the molar ratio of the element A is 0.006%-7%, and the chemical formula of the nickel-manganese precursor is Ni x1 Mn y1 T r (OH)2, wherein 0.225≤x1≤0.275, 0.725≤y1≤0.775, T is a metal doping element, and 0≤r<0.
1.
5. The method according to claim 4, characterized in that The additive includes one or more of Al2O3, Al(OH)3, polyvinylidene fluoride, WO3, lithium fluoride, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide.
6. The method according to claim 4, characterized in that The chemical formula of the nickel-manganese precursor is Ni 0.25 Mn 0.75 (OH)2.
7. The method according to claim 4, characterized in that The molar ratio of lithium in the lithium salt to the metal element in the nickel manganese precursor is 0.48-0.55:
1.
8. The method according to claim 4, characterized in that The sintering temperature is 700° C.-1100° C., and the sintering time is 8 h-14 h.
9. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 3.
10. An electrical device, characterized in that: The secondary battery according to claim 9 is included.
Citation Information
Patent Citations
Modified lithium nickel manganese oxygen material, preparation method of modified lithium nickel manganese oxygen material, and lithium ion battery
CN104425810A
Cobalt-free spinel nickel lithium manganate positive electrode material and preparation method and application thereof
CN115133005A
Positive electrode material of lithium battery as well as preparation method and application of positive electrode material
CN116130643A
Positive electrode active material and preparation method thereof, battery and electric device
CN119069688A
Spinel nickel lithium manganate oxide material and preparation method thereof
US20240262712A1
Cited By
Positive electrode material and preparation method thereof, electrochemical device and electronic equipment
CN120674482A